Social network influences on employee responses to organizational withdrawals - Frank Siedlok; Paul Hibbert; Fiona Whitehurst (Organization Management Journal (OMJ), 2020)
Purpose - The purpose of this paper is to develop a more detailed understanding of how embedding in different social networks relates to different types of action that individuals choose in the context of organizational closures, downsizing or relocations. To develop such insights, this paper focuses on three particular types of social networks, namely, intra-organizational; external professional and local community networks. These three types of networks have been frequently related to different types of action in the context of closures and relocations. Design/methodology/approach - This is a conceptual paper. The authors develop the argument by integrating relevant recent literature on the salience related to embedding in different types of social networks, with a particular focus on responses to organizational closure or relocation. Findings - The authors argue that at times of industrial decline and closure: embeddedness in intraorganizational networks can favor collective direct action; embeddedness in professional networks is likely to favor individual direct action and embeddedness in community networks can lead to individual indirect action. The authors then add nuance to the argument by considering a range of complicating factors that can constrain or enable the course (s) of action favored by particular combinations of network influences. Originality/value - On a theoretical level, this paper adds to understandings of the role of network embeddedness in influencing individual and collective responses to such disruptive events; and direct or indirect forms of response. On a practical level, the authors contribute to understandings about how the employment landscape may evolve in regions affected by organizational demise, and how policymakers may study with or through network influences to develop more responsible downsizing approaches.
Keywords: 650; Social networks; Employment; Embeddedness; Embedding; Organizational demise; Community